The Role of Midwifery in Improving the Success of Exclusive Breastfeeding: A Systematic Literature Review - Ratih Subekti; Olyvia Rosalia (PT. Anagata Sembagi Education, 2025)
This study presents a systematic literature review exploring the multifaceted role of midwives in enhancing exclusive breastfeeding practices. Drawing from 64 peer-reviewed sources, the research highlights how midwives transcend clinical responsibilities to become pivotal agents of education, emotional support, and community mobilisation. Key findings reveal that midwifery-led education significantly boosts maternal knowledge and awareness, while psychological counselling increases mothers’ confidence and perseverance in breastfeeding. Additionally, midwives play a crucial role in addressing physical and technical challenges that often hinder breastfeeding continuation. Their involvement in community empowerment initiatives and their interpersonal communication skills further amplify their impact, fostering environments that support sustained breastfeeding practices. However, systemic limitations such as inadequate training, workforce shortages, and lack of policy reinforcement frequently obstruct midwives from delivering optimal support. These insights underscore the urgent need for structural reforms that empower midwives with the tools, training, and institutional backing required to effectively promote exclusive breastfeeding. Overall, the study reinforces the critical and multi-dimensional role of midwives as both health practitioners and change agents in maternal and child health strategies.